The management of constipation-related functional gastrointestinal disorder (constipation-predominant irritable bowel syndrome) - Amal F Radwan; Nagwa R Ahmed; Eman A Sultan (SpringerOpen, 2015)
The terminology constipation-related functional gastrointestinal disorders was applied to embrace two conditions - constipation-predominant irritable bowel syndrome (IBS-C) and chronic constipation - because of the similarity in the etiology between the two conditions. The cardinal symptoms of IBS-C are abdominal pain or discomfort associated with constipation. The current symptom-based Rome III criteria are used to confirm the diagnosis. Many patients with IBS-C initially treat their symptoms with lifestyle modifications and exclusion diets, together with treatment of symptoms such as constipation by using fiber supplements, over-the-counter laxatives, or probiotics. Less commonly, the patients may also undergo various forms of psychotherapy. Despite these therapeutic modalities, many IBS patients are disappointed with their symptomatic response. There are several drugs that are being proposed for its treatment in the future, one of which is linaclotide, a 14-amino acid synthetic peptide that improves stool frequency and consistency and intestinal transit. Four-week treatment with Bifidobacterium lactis showed superior Results when compared with placebo in decreasing the abdominal distention and improving orocecal and colonic transit.